Arbutin as a Skin Depigmenting Agent with Antimelanogenic and Antioxidant Properties - Boo, Yong Chool (Antioxidants (Basel), 2021)
Arbutin is a compound of hydroquinone and D-glucose, and it has been over 30 years since there have been serious studies on the skin lightening action of this substance. In the meantime, there have been debates and validation studies about the mechanism of action of this substance as well as its skin lightening efficacy and safety. Several analogs or derivatives of arbutin have been developed and studied for their melanin synthesis inhibitory action. Formulations have been developed to improve the stability, transdermal delivery, and release of arbutin, and device usage to promote skin absorption has been developed. Substances that inhibit melanin synthesis synergistically with arbutin have been explored. The skin lightening efficacy of arbutin alone or in combination with other active ingredients has been clinically evaluated. Combined therapy with arbutin and laser could give enhanced depigmenting efficacy. The use of arbutin causes dermatitis rarely, and caution is recommended for the use of arbutin-containing products, especially from the viewpoint that hydroquinone may be generated during product use. Studies on the antioxidant properties of arbutin are emerging, and these antioxidant properties are proposed to contribute to the skin depigmenting action of arbutin. It is hoped that this review will help to understand the pros and cons of arbutin as a cosmetic ingredient, and will lead to future research directions for developing advanced skin lightening and protecting cosmetic products.